2021
DOI: 10.1002/jhet.4422
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and insecticidal evaluation of novel anthranilic diamides of N‐pyridylpyrazole derivatives containing 3‐thioethers

Abstract: Thioether and its derivatives are important active pharmacophores, widely adopted in the molecular design of agrochemicals. The introduction of thioether into drug intermediate is important to improve the liposolubility, hydrophobicity, and bioactivity of molecules. For development of novel insecticides targeting at ryanodine receptor (RyR), a series of anthranilic diamides of N‐pyridylpyrazole derivatives containing 3‐thioether were designed and synthesized. The structures of these compounds were verified usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…67 Furthermore, Sun Peng-wei and co-workers found compound 64 exhibited good insecticidal activities against M. separata at 5 mg/L. 68 Bioassay results indicated that some of the compounds synthesized by Hua Xue-wen and co-workers incorporated a N-cyanomethylsulfilimine on the pyrazole (compound 65), 69 possessed certain degrees of insecticidal activities against M. separata.…”
Section: Part Bmentioning
confidence: 99%
“…67 Furthermore, Sun Peng-wei and co-workers found compound 64 exhibited good insecticidal activities against M. separata at 5 mg/L. 68 Bioassay results indicated that some of the compounds synthesized by Hua Xue-wen and co-workers incorporated a N-cyanomethylsulfilimine on the pyrazole (compound 65), 69 possessed certain degrees of insecticidal activities against M. separata.…”
Section: Part Bmentioning
confidence: 99%
“…Thienopyrimidine, with anti-inflammatory and antimicrobial properties, has widespread applications in the fields of tumour inhibition, anti-tuberculosis, the treatment of acute myocardial infarction and pet repellent [42][43][44]. However, beyond these established applications, our research has unveiled an untapped potential of this compound, its fluorescence.…”
Section: Introductionmentioning
confidence: 99%